The man-leopard murders - Pratten, D (Edinburgh University Press, 2007)
This book is an account of murder and politics in Africa, and an historical ethnography of southern Annang communities during the colonial period. Its narrative leads to events between 1945 and 1948 when the imperial gaze of police, press and politicians was focused on a series of mysterious deaths in south-eastern Nigeria attributed to the 'man-leopard society'. These murder mysteries, reported as the 'biggest, strangest murder hunt in the world', were not just forensic but also related to the broad historical impact of commercial, Christian and colonial aid relations on Annang society.